ENHANCING CORROSION RESISTANCE: A COMPREHENSIVE STUDY ON STAINLESS STEEL AISI 304 - Farkha Nur Alifah; Vera Pangni Fahriani (Jurnal Dinamika Vokasional Teknik Mesin, 2025)
The selection of metal as a construction material used for the industrial world is an important factor that is in accordance with industrial provisions. Corrosion is a factor that must be considered due to the corrosion impact of damage can cause losses in various aspects. AISI 304 stainless steel is one of the stainless steel materials that is resistant to corrosion so that it is widely used in several industries. The corrosion protection in AISI 304 stainless steel has to be carried out with the method of using corrosion inhibitors and protective coatings so that it can reduce damage and extend the life of the AISI 304 stainless steel metal material. Electrochemistry and weight loss methods are used in testing so that the corrosion rate of AISI 304 stainless steel material can be known in various temperature, salinity, and electrolyte solution. The results of temperature variations show that the corrosion rate decreases with increasing temperature and immersion time. The results showed that the higher salinity level of the water media produced the higher the corrosion rate. In the variation of electrolyte solution, the best corrosion resistance of AISI 304 stainless steel occurs in electrolyte solutions with low concentrations. In addition, the mechanical loading study indicates that the magnitude of the loading causes the corrosion rate to increase. In this case, to inhibit corrosion by considering temperature factors, water salinity media environment, chemical substances around the material, and mechanical loads, it is important to carry out corrosion protection in order to slow down the corrosion rate so that it is more effective in its application, minimize damage and loss and extend the life of the AISI 304 stainless steel metal material used sector, the selection of metal as a construction material used for the industrial world is an important factor that is in accordance with industrial provisions. Corrosion is a factor that must be considered because the impact of damage due to corrosion can cause losses in various aspects. The construction material in the industry that is widely used is stainless steel. AISI 304 stainless steel is one of the stainless steel materials that is resistant to corrosion so that it is widely used in several industries. In AISI 304 stainless steel, corrosion protection needs to be carried out with the method of using corrosion inhibitors and protective coatings so that it can reduce damage and extend the life of the AISI 304 stainless steel metal material. The literature study used is a compilation method supported by data collection from various published journals. Electrochemistry and weight loss methods are used in testing so that the corrosion rate of AISI 304 stainless steel material can be known in various conditions and provide knowledge related to how research on AISI 304 stainless steel protection against corrosion can be applied effectively in reducing damage so that it slows down the corrosion rate of AISI 304 stainless steel.